ANALISIS EFISIENSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI PASAR SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN PEKALONGAN TAHUN 2017-2021 - Anni Safitri; Fangela Myas Sari (Politeknik Negeri Semarang, 2022)
This study uses descriptive statistical methods. The analytical tool used is using the formula for efficiency, effectiveness, and market retribution contributions with 2017-2021 data. The examples used are Market Retribution Revenue Data, Market Levies Collection Cost Data, and Pekalongan Regency Original Regional Revenue (PAD) data obtained from the Industry & Trade Office and the Pekalongan Regency Regional Financial Management Agency.The results of this study indicate that the efficiency level of market retribution revenue in 2017-2021 is classified as very efficient with an average of 3.95%. The level of acceptance of market retribution in 2017-2021 is classified as less effective with an average acquisition of 82.07%. The contribution of market levies to Pekalongan Regency's original regional income (PAD) in 2017-2021 is classified as less large with an average of 1.54%.